A PERANAN INKUBASI BISNIS DAN EKONOMI KELEMBAGAAN PADA PROSES PEMBENTUKAN KOPERASI WANITA PERTAMA DI PROVINSI DKI JAKARTA - Chandra, Dicky; Akbari, Deni Adha (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2020)
PKH encourages KM to have access to basic social services of health, education, food and nutrition, and other protection programs. However, the results of this program are still far from expected. The Ministry of Social Affairs through the collaboration between the Central Jakarta Social Service Office and the Muhammadiyah Prof. Dr. HAMKA University has started its first step with the theme